2019
DOI: 10.1016/j.sjbs.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

The impact and effectiveness of faculty development program in fostering the faculty’s knowledge, skills, and professional competence: A systematic review and meta-analysis

Abstract: Background Faculty vitality is the main ingredient to enhance professional education and competence. Enriching the faculty vitality in key domains of teaching, assessing, research, professionalism, and administration is perceived to improve educational environment significantly and enhances the academic performance of learners. Faculty development program (FDP) has been considered as a stand-alone educational pedagogy in fostering knowledge and professional skills of faculty. However, few studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 53 publications
1
49
0
Order By: Relevance
“…Besides, studies have pointed out that the development of attitudes can be facilitated by providing a conductive atmosphere and models. In other hand, presence of faculty development programs (FDP) and "teaching the teacher courses" will affect the personal and professional behavior of the faculties (3,28); this was the dominant aspect of this FDP.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, studies have pointed out that the development of attitudes can be facilitated by providing a conductive atmosphere and models. In other hand, presence of faculty development programs (FDP) and "teaching the teacher courses" will affect the personal and professional behavior of the faculties (3,28); this was the dominant aspect of this FDP.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Kamel (2016), it was found that professional FDP improves teaching skills in higher education by producing promising outcomes in the learning and teaching practices. Also, Bilal, Guraya and Chen (2017), in their study investigating the impact and effectiveness of FDP on faculty members' knowledge and competencies, found that FDP creates a significant and positive impact in enhancing faculty's knowledge and professional competence. Lastly, in the study of Dee and Daly (2009), it was shown that FDPs produce positive impact on teaching and learning, most especially when they are grassroots initiatives led by the faculty, when they promote inclusivity in teaching and learning, when they foster curricular and pedagogical transformation and multidisciplinary representation, and when they build connections and collaborations between and among stakeholders of higher education institutions.…”
Section: Faculty Development Programs In Higher Educationmentioning
confidence: 99%
“…The use of different teaching methodologies help an educator to accommodate students' learning styles, which might have a positive impact on the academic performances of nurse and midwife educators resulting in enrichment of students' competencies (Bilal, Guraya, & Chen, 2017;Boström & Hallin, 2013).…”
Section: Discussionmentioning
confidence: 99%